Microfluidic Approaches for Isolation, Detection, and Characterization of Extracellular Vesicles: Current Status and Future Directions - Gholizadeh, Shima (Biosens Bioelectron, 2016)
Extracellular vesicles (EVs) are cell-derived vesicles present in body fluids that play an essential role in various cellular processes, such as intercellular communication, inflammation, cellular homeostasis, survival, transport, and regeneration. Their isolation and analysis from body fluids have a great clinical potential to provide information on a variety of disease states such as cancer, cardiovascular complication and inflammatory disorders. Despite increasing scientific and clinical interest in this field, at the time of writing there are still no standardized procedures available for the purification, detection, and characterization of EVs. Advances in microfluidics allow for chemical sampling with increasingly high spatial resolution and under precise manipulation down to single molecule level. In this review, our objective is to give a brief overview on the working principle and examples of the isolation and detection methods with the potential to be used for extracellular vesicles. This review will also highlight the integrated on-chip systems for isolation and characterization of EVs.